2022
DOI: 10.17507/jltr.1306.02
|View full text |Cite
|
Sign up to set email alerts
|

Online and Offline Assessment Methods in Higher Education: A Revisitation of EFL Teachers’ Perceptions and Practices

Abstract: Assessment is a key component of the educational spectrum and engages teachers in evaluating students’ performance through various methods. During the Covid-19 pandemic, teachers employed various assessment methods through the online mode of teaching and learning; now, at the beginning of the end of the pandemic, teachers are back to practicing offline assessment methods. This study identifies English as a foreign language (EFL) teachers’ perceptions of online versus offline assessment methods in higher educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to Sulistyowati et al (2022), students valued a comfortable environment during online learning. The results also showed that students in the current study had medial attitudes toward learning EFL listening and speaking skills via Blackboard in terms of not having enough time to participate in virtual sessions and the possibility of cheating and other unethical practices, which may not reflect students' real performances (Alzubi et al, 2022;Nazim & Ali, 2022). This result accords with that of Alzamil (2021), who found that respondents had positive attitudes toward online learning in EFL speaking.…”
Section: Discussion the First Research Question: What Are The Pre-uni...mentioning
confidence: 72%
“…According to Sulistyowati et al (2022), students valued a comfortable environment during online learning. The results also showed that students in the current study had medial attitudes toward learning EFL listening and speaking skills via Blackboard in terms of not having enough time to participate in virtual sessions and the possibility of cheating and other unethical practices, which may not reflect students' real performances (Alzubi et al, 2022;Nazim & Ali, 2022). This result accords with that of Alzamil (2021), who found that respondents had positive attitudes toward online learning in EFL speaking.…”
Section: Discussion the First Research Question: What Are The Pre-uni...mentioning
confidence: 72%
“…These concerns include a lack of trust in the proficiency evaluation online, the absence of quality goal orientation, student learning preference variety, poor professional preparedness initiatives, and student motivation. Various studies regarding the effectiveness of evaluating student proficiency in a fully online setting (Blake, 2015;Alzubi et al, 2022;Algraini, 2023). Yantraprakorn (2018) noted explicit student criticisms of their online university language program.…”
Section: Online Language Learning Effectivenessmentioning
confidence: 99%
“…The way HEIs implemented assessments already started to show fractures pre-COVID-19 (Alzubi et al, 2022). Many higher education institutions rely on traditional assessment methods, such as examinations and standardised tests.…”
Section: Introductionmentioning
confidence: 99%